Assessing grazing intensity plant frequency in Kordofan Region - Hamed, Yousif Mohamed Zainelabdeen; Khatir, Abdelrahman A; Mohamed, MAM; Mohamed, Khalid H; Eltome, Ahmed IA (International Journal of Environment, 2015)
This study was conducted in Um "Nabag" (15km north of "Bara"), "Dilling" (160km south of "Elobeid") and "Eldemiokya" (30km east of "Elobeid"). The main objective of this study is to assess the effect of grazing on growth performance of natural rangelands in Kordofan region. The specific objectives: To assess the effect of grazing level on vegetation frequency. The results showed different levels of grazing intensity at different sites as indicated by plants frequency and biomass. Intensive grazing levels were found at Bara in the north, early and late in the rainy season but in Dilling it was not found in the late in the rainy season for both seasons (2008 and 2009) which indicated longer stay of herders in "Bara" area as a rainy season residences. Frequency of the species between non- grazed and grazed areas showed a decrease for the two seasons especially for preferred species at the different sites as in the case of Eragrostis termula and Cenchrus biflorus in (2008 ),Similar results were observed in (2009) with Fimbirsty dichotomo and Cenchrus biflorus. The study recommended that grazing level can be used as practical mean to assess utilization level as expressed by growth performance indicators including frequency. Level (II) is expected to result in negative impact on rangeland plants growth performance. DOI: http://dx.doi.org/10.3126/ije.v4i2.12622 International Journal of Environment Vol.4(2) 2015: 27-37